Attitudinal Meaning Analysis Based on Linguistic Corpus in Parenting Text Translation - Riris Mutiara Simamora (SAWERIGADING, 2024)
The depiction of language used in parenting books becomes important to study because parenting books are one of the information media used by parents to obtain guidance, knowledge, and direction in child rearing. This research is aims to examine how parents and children are portrayed in parenting books by assessing the expressions that appear in the text, both in the Source Text (ST) and the Target Text (TT). The research method used is qualitative descriptive using the appraisal theory by Martin White (2005) with the assistance of AnCont 3.5.9 (Windows) 2020 Corpus Linguistics. The data source used is a parenting book by Philippa Perry, published by Penguin Life titled "The Book You Wish Your Parents Had Read (and Your Children Will be Glad That You Did)" published in 2019, as the ST. This book was translated into Indonesian by Leinovar, published by Renebook with the title, "The Book You Wish Your Parents Had Read (Orangtuamu Wajib Baca Buku Ini, dan Anakmu Akan Senang Jika Kamu Membacanya)" in 2022, as the TT. This research was conducted by analyzing the forms of emotion in the text based on attitude categories. It is found that parents in the ST tended to be depicted with negatively charged affect expressions (17 findings), while in the TT, parents were depicted with a dominant negative judgment attitude (25 findings). In the ST, the portrayal of children is mostly positively judged, with 41 findings. In the TT, the dominant expression found is negative judgment, with 35 findings. In terms of collocation categories, the word "parents" in the ST is predominantly collocated with "to-", while in the TT, the most dominant collocation word is "yang". The word "children" in the TT is dominated by repeated words. Differences in expressions can be influenced by differences in translation strategies. Three translation patterns were found in the text: addition, omission of information, and shifting of evaluated items.